Evaluation of Three Forest-Based Bioenergy Development Strategies in the Inland Northwest, United States. Issue 6 (17th September 2018) - Saul, Darin; Newman, Soren; Peterson, Steven; Kosse, Eli; Jacobson, Ryan; Keefe, Robert; Devadoss, Stephen; Laninga, Tammy; Moroney, Jill
Abstract: In this article, we compare three bioenergy scenarios that use woody biomass from US Inland Northwest forests. The scenarios are based on current bioenergy research, development efforts, and stakeholder input. They include a small-scale system that produces drop-in transportation biofuel and biochar, a large, regional system that produces bio-aviation fuel, and a midsized pellet production system. We modeled woody biomass harvest, processing, and transportation, and then evaluated profitability and potential socioeconomic impacts to determine the overall viability of each strategy. Through interviews, we found widespread stakeholder support for all three scenarios. Wood-pellet production was profitable and feasible with current prices and conditions, whereas liquid biofuel production was profitable only at levels that greatly exceed current prices.